2016
DOI: 10.1002/stem.2333
|View full text |Cite
|
Sign up to set email alerts
|

Plant Homeo Domain Finger Protein 8 Regulates Mesodermal and Cardiac Differentiation of Embryonic Stem Cells Through Mediating the Histone Demethylation of pmaip1

Abstract: Histone demethylases have emerged as key regulators of biological processes. The H3K9me2 demethylase plant homeo domain finger protein 8(PHF8), for example, is involved in neuronal differentiation, but its potential function in the differentiation of embryonic stem cells (ESCs) to cardiomyocytes is poorly understood. Here, we explored the role of PHF8 during mesodermal and cardiac lineage commitment of mouse ESCs (mESCs). Using a phf8 knockout (ph8 -/Y ) model, we found that deletion of phf8 in ESCs did not af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…To model mental retardation in humans with PHF8 deficiency, we generated Phf8 knockout (KO) mice by targeting the exons 7 and 8 encoding the core region of mice PHF8. The strategy of generating KO allele was described in detail in previous work 22 . Genotyping results showed recombinase-mediated efficient deletion of exons 7 and 8 in the genome of mutant mice (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To model mental retardation in humans with PHF8 deficiency, we generated Phf8 knockout (KO) mice by targeting the exons 7 and 8 encoding the core region of mice PHF8. The strategy of generating KO allele was described in detail in previous work 22 . Genotyping results showed recombinase-mediated efficient deletion of exons 7 and 8 in the genome of mutant mice (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As a protein deubiquitinase that cleaves ubiquitin linkages from its substrates, USP7 functions to oppose ubiquitinations of various proteins including E3 ligases (MDM2/MDMX [ 35 ] and ICP0 [ 36 ]), chromatin associated factors (DNMT1 [ 37 ], UHRF1 [ 38 ], PHF8 [ 39 ], and Tip60 [ 40 ]), as well as tumor suppressors (p53 [ 41 ], PTEN [ 42 ], and claspin [ 43 ]). Among these targets, histone demethylase PHF8 is a critical epigenetic factor in cell fate determinations of stem cells [ 44 ]. Recently, Han’s study indicated that PHF8 triggered osteogenic differentiation of BMMSCs and facilitated bone formation and regeneration via epigenetically modulating the activity of a nuclear matrix protein, special AT-rich sequence-binding protein 2 (SATB2) [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…R1 and E14 mESCs carrying a Brachyury-GFP (T-GFP) were maintained on mitomycin C-inactivated mouse embryonic fibroblast cells as described previously [5, 21]. Cardiomyocyte differentiation was initiated by a hanging-drop technique [22].…”
Section: Methodsmentioning
confidence: 99%